Sky daddy : a novel - Folk, Kate (Random House, 2025)
"Linda's life may appear drab to those around her: She makes $20 an hour as a content moderator, flagging comments that violate a tech conglomerate's terms and conditions. Every night, she returns to the windowless room she rents in a garage on the outskirts of San Francisco. But once a month, she indulges her true passion: taking the AirTrain to SFO for a clandestine meeting on the cheapest flight out that night. Linda isn't interested in pilots, though. She has a thing for planes; their intelligent windscreens, comely slats, and rumbling turbulence make her feel a way that no man ever could. In fact, she desperately believes her destiny is to marry one by uniting their souls for eternity in what the rest of us may vulgarly refer to as a plane crash-the fatal tailspin caused by the plane's uncontrollable desire for her. Linda's unusual proclivities distance her from the rest of humanity, so she's surprised and pleased when her charismatic work friend, Karina, invites her to a quarterly Vision Board Brunch. She wants to hasten her romantic fate through manifestation, but as her vision boards start coming true a bit too literally, Linda must choose between being her authentic self or abandoning her destiny for a more "normal" life"--